Revelation as an apocalypse: Critical considerations on the literary genre apocalypse - van Niekerk, Robert J.; van Eck, Ernest (Verbum et ecclesia, 2025)
In popular discourse, Revelation is frequently characterised as an apocalyptic text concerned with the cataclysmic end of the world. This article offers a critical overview of historically informed scholarly attempts to define and reconstruct the literary genre of apocalypse and its application to Revelation. A correct understanding of genre bears not only classificatory but also epistemological significance: the manner in which the genre of a text is identified profoundly shapes its reading and interpretation. Key developments in the definition of apocalypse as a literary genre will be examined, beginning prior to the genre-decade and continuing through its course. The influence of this decade’s research is clearly reflected in recent representative historical-critical studies of Revelation. In conclusion, the article notes both the contributions these genre studies have made towards a more responsible and culturally sensitive reading of Revelation, as well as topics that require further investigation. This article is intended as a foundational study for a series of further investigations into Revelation.Intradisciplinary and/or interdisciplinary implicationsBy promoting a more precise, historically conscious and culturally sensitive understanding of the genre apocalypse, this article enables readers to engage with Revelation more responsibly. The study also identifies key areas for further scholarly investigation.